Made of gold - Reyes, Cid (Makati City Metrobank Foundation, 2013)
A showcase of winners of the Metrobank Art & Design Excellence competition throughout Metrobank's 50 years.
FA-2817g donated by Prof. Amando F. Santos on July 16, 2013.
Keywords: Drawing -- Private collections -- Philippines